Right Aortic Arch and Kommerell’s Diverticulum Repaired without Reconstruction of Aberrant Left Subclavian Artery - Hiroshi Osawa; Daisuke Shinohara; Kouan Orii; Shigeru Hosaka; Shoji Fukuda; Okihiko Akashi; Hiroshi Furukawa (Case Reports in Vascular Medicine)
Right aortic arch with Kommerell’s diverticulum is a very rare situation. Surgical treatment is recommended for symptomatic patients or asymptomatic patients with a large diverticulum. However planning the strategy of operation is difficult without a 3D imaging. We report a case of a 57-year-old man with right aortic arch, Kommerell’s diverticulum, and aberrant left subclavian artery. After a 3D-CT imaging, the patient underwent descending aortic replacement without reconstruction of aberrant left subclavian artery. After operation, there was no signs or symptoms of ischemia of the left arm. If the reconstruction of the aberrant subclavian artery was too difficult, closing its orifice is an acceptable decision. It has been found advantageous because of a decrease blood loss and a shorter cardiopulmonary bypass duration. If an ischemia of the arm is noticed, additional reconstruction will have to be considered. 3D-CT imaging was very useful to have a proper orientation and plan for the operative strategy.